Scanning Probe Microscopy Applied to Organic–Inorganic Halide Perovskite Materials and Solar Cells. Issue 1 (19th December 2017) - Hieulle, Jeremy; Stecker, Collin; Ohmann, Robin; Ono, Luis K.; Qi, Yabing
Abstract: To meet the increasing energy demands of the growing society, environmentally friendly and renewable energy sources are needed. Organic–inorganic halide perovskites are a promising class of materials for building solar cells due to their easy fabrication, flexibility, and bandgap tunability. The highest efficiency achieved with these materials in the lab is comparable to conventional silicon solar cells currently on the market. However, their commercialization is hampered by certain challenges, such as stability, lead toxicity, and reproducibility. Inhomogeneities in the perovskite material at the atomic scale are identified as a possible cause of these issues. To study this further, scanning probe microscopy offer a unique real‐space visualization of the sample topography down to the atomic level. Simultaneously, the sample morphology can be correlated to its electronic, chemical, and optoelectronic properties. Here, the latest studies on organic–inorganic halide perovskites using scanning probe microscopy methods such as atomic force microscopy, scanning tunneling microscopy, and scanning near field optical microscopy are reviewed. A comparison of each technique and their specific use in the field of perovskite photovoltaics is provided. Particular focus is given to unraveling specific properties that are relevant for a fundamental understanding of perovskite materials and solar cells. Abstract : Scanning probe techniques such as scanning tunneling microscopy, atomic force microscopy, and scanning near‐field optical microscopy are unique tools to probe the morphology and the electronic and optoelectronic properties of a material. The latest studies on organic–inorganic halide perovskite using scanning probe methods are reviewed. Focus is given to properties relevant for fundamental understanding of perovskite materials and solar cells.